Eksistensi Nilai-Nilai Kearifan Lokal dalam Menghadapi Globalisasi: Kajian Sosio-Kultural Berbasis Studi Literatur - Marisa Meilano Rizki; Sandi H. Pasaribu (Jurnal Pendidikan, Sejarah, dan Budaya, 2026)
This study aims to analyze the existence of local wisdom values in responding to globalization through a socio-cultural perspective based on a systematic literature review. The data were collected from reputable academic publications published between 2015 and 2026, selected based on relevance and methodological rigor. The analysis employed a thematic-critical approach to identify patterns of transformation, integration, and resistance of local wisdom across social and educational contexts. The findings indicate that local wisdom does not undergo absolute marginalization but instead transforms through contextual adaptation, integration into educational systems, and rearticulation within social practices. Globalization presents challenges such as cultural homogenization and commodification, while simultaneously offering opportunities for revitalizing local identity through innovation and community-based strategies. These findings highlight the strategic role of local wisdom as a source of values and knowledge in strengthening cultural resilience and collective identity in the global era.